Risk Factor Analysis of Type 2 Diabetes Mellitus Among Adults Aged ≥25 Years Based on the Health Promotion Model - masdiana; Tressia Febrianti; Desi Afriyanti; Rizki Hidayat (Institut Citra Internasional, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic non-communicable disease with a continuously increasing prevalence and represents a major public health challenge. The occurrence of T2DM is influenced by complex interactions between biological and behavioral factors, highlighting the need for a comprehensive understanding of its risk factors at the primary healthcare level.This study aimed to analyze the association between risk factors and the occurrence of Type 2 Diabetes Mellitus among adults aged over 25 years. This study used an analytical observational design with a cross-sectional approach among adults aged over 25 years in the working area of Pasir Putih Primary Health Center. Data were analyzed using univariate analysis, bivariate analysis with Chi-square tests, and multivariate analysis using multiple logistic regression. The result showed that age (p=0.017), sex (p<0.001), familiy history of diabetes (p=0.006), dietary pattern (p=0.004), and physical activity (p=0.034) were significantly associated with T2DM. Multivariat analysis identified family history diabetes as the most dominant factor (OR=65.04; p=0.006), while low physical activity remained an independent modifiable risk factor (OR=3.97; p=0.034). Dietary pattern showed a protective effect after adjustment (OR=0.018; p=0.004)he occurrence of T2DM is influenced by interactions between biological and behavioral factors, consistent with the Health Promotion Model framework. These findings emphasize the importance of community-based promotive and preventive interventions at the primary healthcare level.